CONTROL OF BIOMASS BOILER WATER TEMPERATUR USING SLIDING MODE CONTROL SYSTEM (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Medium scale biomass temperature control is aspecific field of control issues where one of the most important features is cost effectiveness. It means that anykind of control system improvement should be done withthe lowest possible additional costs. Generally, the basiccontrol of such kind of boiler regulates temperature ofoutlet heating water. This control can be also performed bya conventional or advanced control. Although the main problem of this study is the constructionof the model of biomass boiler for control purposes, our taskdeals with technology of boilers and principles of its innerprocesses as well. Creation of the model comes out not onlyfrom these important findings, but also from experimentaldata collected during measurements in real operation. Heatand mass balance calculations were made according to thesedata and they serve to precise dynamic properties ofexperimental unit for biomass combustion.Based on the derived mathematical model of the biomassboiler, here is possibility to enhance the control byadditional algorithms that are responsible for extendedoptimization functions. In this paper, an advanced processcontrol such as sliding mode control system (SMC) is usedto control the temperature of the boiler water. The resultsshow that SMC has strong immunity for the disturbanceand the varying of process parameters.